THE EFFECT OF THE CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER AND GROSS PROFIT MARGIN ON THE REMAINING RESULTS OF THE COOPERATIVE'S OPERATIONS (CASE STUDY ON KP-RI GKK AIRTIRIS 2010-2019) - Fiqri Hafidz; Syamsul Bahri; Mustafa Kamal (STIE Bangkinang Publishing, 2020)
This research was conducted to determine the effect of the variable current ratio, debt to equity ratio, total assets turnover and gross profit margin simultaneously or partially on the remaining business results of KP-RI GKK Airtiris. The population in this study were all financial reports of the KP-RI GKK Airtiris. Meanwhile, the sample in this study is the financial statements of the KP-RI GKK Airtiris during the study period. Data collection techniques using the method of observation, file research, and interviews from cooperatives. Hypothesis testing uses multiple linear regression analysis with the help of SPSS V.23.00 for windows. Based on the results of the study, it shows that the variable Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Gross Profit Margin simultaneously affect the Remaining Operating Results. While partially, namely the variable Debt to Equity Ratio, Total Assets Turnover and Gross Profit Margin which affect the Remaining Operating Results, while the Current Ratio variable has no effect on the Remaining Operating Results.